Iron Concentration Does Not Differ in Blood but Tends to Decrease in Cerebrospinal Fluid in Parkinson’s Disease - Shen, Xiaoli; Yang, Huazhen; Zhang, Dongfeng; Jiang, Hong (Frontiers in Neuroscience, 2019)
Background: Iron accumulation in the substantia nigra in PD patients was acknowledged, but the studies on alteration of iron levels in blood and cerebrospinal fluids (CSF) reported inconsistent results. Objective: To determinate the alterations of blood and CSF levels of iron in PD patients, a case-control study and a meta-analysis both in blood and CSF were conducted. Methods: In the case-control study, 43 PD patients and 33 controls were recruited to test iron metabolism, 15 normal and 12 PD patients donated CSF. Levels in iron were quantified by inductively coupled atomic emission spectrometry. Iron metabolism was analyzed by routine blood tests. In the meta-analysis, a comprehensive literature search was performed on relevant studies published from Jan 1980 to Dec 2018 in PubMed, Web of Science and EMBASE databases. The pooled standard mean difference (SMD) with random effects model was selected to estimate the association between iron levels and PD. Results: In the case-control study, the iron level in serum in the controls and PD patients were 110.00±48.75 μg/dl and 107.21±34.25 μg/dl, respectively, no significant difference was found between them (p=0.850), with a small effect size (Cohen’s d: 0.12; 95% CI: 0.08-0.17). Ferritin level in PD patients was lower than controls (p=0.014). The CSF levels of iron in control and the PD patients were 20.14±3.35 ng/dl and 16.26±4.82 ng/dl, respectively. CSF levels of iron were lower in PD compared with that of controls (p=0.021), with a moderate effect size (Cohen’s d: 0.51; 95% CI: 0.43-0.65). In the meta-analysis, 22 eligible studies and a total of 3607 participants were identified. Blood levels of iron did not differ significant between PD patients and the controls [SMD (95%CI): -0.03 (-0.30, 0.24)], but CSF iron levels tended to be lower in PD patients compared with that in the controls [SMD (95%CI): -0.33 (-0.65, -0.00)]. Conclusions: Iron homeostasis may be disturbed in CSF, but not in the peripheral blood in PD.